Perspectives: Making South African historians count (Historia, 2021)
In August 2019, economist Johan Fourie of Stellenbosch University invited Historia to publish a “reflection piece” he had written and presented in March that year at the University of the Free State. In it, he puts forward his views of what History does, what it ought to do, and how it can perhaps be done better here in (South) Africa. His central concern is with big data and digitising records. He issues a number of seemingly bold challenges and provocations to historians. A slightly edited version of that piece is reproduced below. Rather than publish it as a stand-alone piece, however, and in the spirit of respectful exchange, we are publishing four substantial engagements with several of the arguments made by Fourie. These responses are by Faeeza Ballim, Gerald Groenewald, Jennifer Upton and Tinashe Nyamunda, all of whom are experts in their respective fields and experienced in their craft. Each takes the substantive points made by Fourie seriously, and responds to them in different ways. Best read as perspectives on a complex and enduring debate amongst people who are mindful of the politics of the past as well as being critically engaged with what historians “do” in the present, they recognise the technological and methodological promises of digital histories and big data, but eloquently remind us too of their limitations and indeed their potential pitfalls. There is much more to discuss, not the least of which is the responsibility for the ownership of and access to such records in a democratic and socially just world. The authors’ information is included at the close, after a brief “Response” by Fourie.
Keywords: History; big data; digitising records; Johan Fourie; African economic history; knowledge production; historians